The Adoption of Non-Rival Inputs and Firm Scope - Xian Jiang; Hannah Rubinton (Center for Economic Studies and ifo Institute (CESifo), 2024)
Custom software is distinct from other types of capital in that it is non-rival—once a firm makes an investment in custom software, it can be used simultaneously across its many establishments. Using confidential U.S. Census data, we document that while firms with more establishments are more likely to invest in custom software, they spend less on it as a share of total capital expenditure. We explain these empirical patterns by developing a model that incorporates the non-rivalry of custom software. In the model, firms choose whether to adopt custom software, the intensity of their investment, and their scope, balancing the cost of managing multiple establishments with the increasing returns to scope from the non-rivalrous custom software investment. Using the calibrated model, we assess the extent to which the decline in the rental rate of custom software over the past 40 years can account for a number of macroeconomic trends, including increases in firm scope and concentration.
Keywords: D24; E22; O33; 330; technology adoption; non-rivalry; concentration; firm scope